Seasonal DXA-measured body composition changes in professional male soccer players - Milanese, C.; Cavedon, V.; Corradini, G.; De Vita, F.; Zancanaro, C. (Journal of Sports Sciences, 2015)
This work investigated changes in body composition of professional soccer players attending an Italian Serie A club across the competitive season; it is original insofar as body composition was assessed at multiple time points across the season using the accurate three-compartment model provided by Dual-Energy X-Ray Absorptiometry (DXA). Thirty-one players (4 goalkeepers, 13 defenders, 8 midfielders, 6 forwards) underwent DXA and anthropometry at pre-, mid- and end-season. One operator measured whole body and regional body composition (fat mass, FM; fat-free soft tissue mass, FFSTM; mineral mass). Two players were excluded from analysis due to serious injury. Data were analysed with repeated measures ANOVA; factors were season time point and playing position. Results showed that whole-body FM and %FM significantly (P < 0.001) decrease at mid-season (-11.9%; -1.3%, respectively) and end-season (-8.3%; -0.8%, respectively) whereas FFSTM significantly (P < 0.001) increase at mid-season (+1.3%) and end-season (+1.5%). Limited, but significant changes took place in bone mineral content. Some regional (upper and lower limbs, trunk) differences in the pattern of body composition changes across the season were also found. Changes were similar for all playing positions. It was concluded that professional soccer players undergo changes in their FM, FFSTM, and mineral mass across the season with some regional variations, irrespective of the playing position. Changes are mostly positive at mid-season, possibly due to difference in training between the first and second phase of the season.